Membangun Karakter Tanggung Jawab Siswa SD melalui Pembelajaran Tematik PPKn: Peran Strategis Guru Kelas - Wa Ode Nisra; Bambang Sumardjoko; Yulia Maftuhah Hidayati; Laili Etika Rahmawati; Minsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to analyze the role of teachers in developing the character of responsibility in thematic learning of Pancasila and Civics Education (PPKn) content in grade III elementary school. This research uses a qualitative approach. Data were collected through observation, in-depth interviews with classroom teachers, and analysis of learning documents. The results showed that teachers have a central role in shaping the character of responsibility through various teaching strategies, such as giving assignments that require individual and group responsibility, and implementing positive discipline in the classroom. Teachers also act as role models in demonstrating an attitude of responsibility, which is exemplified through consistency in daily rules and behavior. Thematic learning with Civics content has proven to be effective in integrating responsibility values, because it allows students to understand concepts in a broader context and is relevant to everyday life. In addition, the involvement of parents and the community in the learning process also strengthens the cultivation of responsibility character. This study concludes that the role of teachers is crucial in the formation of responsible character in students.